Pretreatment of forage legumes under moderate salinity with exogenous salicylic acid or spermidine - Neto, Antonio Pizolato [UNESP]; Alves, Rita de Cassia [UNESP]; Viana Camargos, Ayza Eugenio [UNESP]; Gratao, Priscila Lupino [UNESP]; Raymundo Carregari, Sonia Maria [UNESP]; Zingaretti, Sonia Marli; Mathias Dos Santos, Durvalina Maria [UNESP] (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2020)
The present study aims to determine whether exogenous salicylic acid (SA) or spermidine (Spd) has any protective effect against salt stress. Seeds were subjected to 0, 20, 40, and 60 mM NaCl with or without salicylic acid or spermidine (0.5 mM) for 10 days. The evaluated variables were germination rate, shoot and root dry masses, glycine betaine content, lipid peroxidation, and the activities of superoxide dismutase (SOD), catalase (CAT), and ascorbate peroxidase (APX). The data were subjected to Tukey's test (p <= 0.05). There was a growth increase, especially in plant shoots. The reduction in lipid peroxidation, as indicated by lower malondialdehyde (MDA) levels, can be explained by an increase in antioxidant activity when SA and Spd were added. When compared to CAT and APX, SOD was the least responsive enzyme to the addition of both SA and Spd in salt-stressed plants. SA and Spd partially reduced the effects of moderate salt stress in both plant species; however, Spd addition had better results than SA in terms of suppressing oxidative stress. Lablab plants were more vigorous than pigeonpea plants.
Keywords: Cajanus cajan; Dolichos lablab; salt stress; glycine betaine; oxidative stress; growth